The relationship between multi-objective robustness concepts and set-valued optimization - Ide, Jonas; Köbis, Elisabeth; Kuroiwa, Daishi; Schöbel, Anita; Tammer, Christiane (Fixed point theory and applications (Hindawi Publishing Corporation), 2014)
In this paper, we discuss the connection between concepts of robustness for multi-objective optimization problems and set order relations. We extend some of the existing concepts to general spaces and cones using set relations. Furthermore, we derive new concepts of robustness for multi-objective optimization problems. We point out that robust multi-objective optimization can be interpreted as an application of set-valued optimization. Furthermore, we develop new algorithms for solving uncertain multi-objective optimization problems. These algorithms can be used in order to solve a special class of set-valued optimization problems.